Facile construction Z-scheme anatase/rutile TiO2/g-C3N4 hybrid for efficient photocatalytic H2 evolution under visible-light irradiation. Issue 24 (15th December 2022) - Zhang, Guang-Hui; Zhang, Hao-Ran; He, Jian-Guo; Jiang, Yi-Chen; Zhang, Huo-Li; Zhou, Qi-Bo; Cao, Jian-Liang
Abstract: Z-scheme anatase/rutile TiO2 /g-C3 N4 hybrids (denoted as LTARCN-x, x represents calcination temperature) were designed and synthesized by growing TiO2 nanorods on the surface of g-C3 N4 utilizing impregnation-calcination method. Furthermore, through the etched effect of hydrochloric acid and calcination treatment, the as-prepared LTARCN-x possessed abundant pore structure and larger surface area, and the surface area of LTARCN-425 was 8.5 times than that of bulk g-C3 N4 . Meanwhile, the g-C3 N4 would play a role of carrier to prevent from the aggregation of TiO2 nanorods. In addition, under visible light irradiation, the Z-scheme heterostructure would be constructed between the rutile TiO2 nanorod and g-C3 N4 nanosheet, respectively. The optimized photocatalyst LTARCN-425 exhibited a preferable activity, the photocatalytic hydrogen production rate of LTARCN-425 was about 1031 μmol g −1  h −1, and it was about 6.3 and 13.6 times than that of g-C3 N4 and TiO2, respectively. Moreover, the photocatalytic mechanism of the hydrogen production was studied intensively via designing fluorescent probe, Pt and PbO2 deposition experiment, and the characterizations of EPR, TEM, HRTEM and XPS.